Territorio y colonialidad: gentrificaciones ontoepistémicas contemporáneas - Yedaide, Maria Marta (2025)
The current processes of re-territorialization in Abya Yala expose colonial marks which remain alive in the ways of meaning, inhabiting and managing territories. This article socializes current doctoral research work about the meanings of education that trigger certain agencies in university extension projects. We originally defined the relationships between the academic and broader communities in terms of inter-territoriality, which enabled the recognition of the (de) colonial tension legacy-resistance in the treatment of otherness, as well as the concomitant epistemic gentrification. As the literary review and the fieldwork developed, however, we felt the need to explore neomaterialisms, neovitalisms and posthumanisms, as well as autoethnography, in methodological terms, to fulfil the promise of the ontological turn that (de)colonial perspectives have been announcing for decades now. Based on new definitions of territory, we hereby advance the value of Abya Yala and re-existence as powerful agencies to create new attention regimes to address contemporary educational relationships in university extension in intra and trans-territorial terms.